(untitled) (Research, Society and Development, 2022)
The Brazilian flora harbors extensive plant biodiversity with the possibility of therapeutic use. In this context, the genus Aristolochia is widely used in folk medicine. From this perspective, the study aims to demonstrate important characteristics of these vegetables in the current literature. It was observed that the genus has promising medicinal properties that are directly related to its biological and chemical composition. However, it is notable that more research is needed to guide the safe use and encourage the synthesis of new pharmaceutical products derived from these herbs.